PENGANGKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL DALAM PERSPEKTIF PERATURAN PEMERINTAH NOMOR 78 TAHUN 2013 - Nata, M Nasir (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2016)
Since the enactment of the Act Number 32 of the Year 2004 regarding Regional Government, especially after the enactment of the Government Regulation Number 48 of the Year 2005 regarding the Appointment of the Honorary Employees to become the candidates of civil servants, the implementation of village administration began to be problematic. This problem is caused by the demands of the Village Head and Village Secretary for equal rights to be equalized with the Civil Servants. This demand implicates the birth of the Government Regulation Number 45 of the Year 2007 on the Requirements and Procedures for the Appointment of a Village Secretary to be a Civil Servant, and theoretically this regulation contradicts the Government Regulation Number 78 of the Year 2013 on the Second Amendment of the Government Regulation Number 98 of the Year 2000 on the Procurement of Civil Servants. Based on the background of this study, the problems are formulated as follows: 1) What is the ratio legis of the appointment of the Village Secretary to be a civil servant in the perspective of the Government Regulation Number 78 of the Year 2013, and 2) What is the reason of the appointment of the Village Secretary to be a civil servant? The formulation of this problem aims to analyze and to find the ratio of legis and the ratio decidendi of the appointment ofÂ the Village Secretary to be a Civil Servant in the perspective of the Government Regulation Number 78 of the Year 2013. Problem analysis of this study indicates that the ratio legis of the appointment of the Village Secretary to be a civil servant is based on the reason that government has an authority to appoint a civil servant, while the reason of the appointment of the Village Secretary to become a civil servant is that it is in accordance with justice principle and legal certainty, that is to satisfy the sense of justice in the society. In order not to cause multiple interpretations, the appointment of civil servants in all sectors should be based on common ground regulation, and the Secretary of the Village should indeed be appointed from the element of civil servants.